Program Patterns and Preferences, and the Workability of Competition in Radio Broadcasting - Steiner, Peter O. (Quarterly Journal of Economics, 1952)
I. Criteria for the appraisal of workability, 195. — II. The one period model, 197. — III. The model over time, 207. — IV. Relevance of the model to the market structure of the industry, 217. — V. Some suggestions for further analysis, 222.